In vitro biotization - M I Yablonskaya; M S Gins; M A Molchanova (RUDN Journal of Agronomy and Animal Industries, 2016)
In vitro coculture of plant tissue explants with beneficial microorganisms enhance their tolerance to abiotic and biotic stresses. The induced resistance response caused by the inoculants is referred to as “biotization”. There is enough experimental evidence with bacteria (bacterization) and vesicular arbuscular mycorrhiza (mycorrhization) inoculations to recommend utilization of this technology in commercial micropropagation. Micropropagated plantlets usually exhibit high mortality rate upon their transfer to soil, so biotization technique can improve survival and is considered to be a perspective method in clonal micropropagation.